Can we challenge attention and interpretation threat biases in rescued child labourers with a history of physical abuse using a computerised cognitive training task? Data on feasibility, acceptability and target engagement. (March 2023) - Dhakal, Sandesh; Gupta, Shulka; Sharma, Narayan Prasad; Upadhyay, Aakanksha; Oliver, Abigail; Sumich, Alex; Kumari, Veena; Niraula, Shanta; Pandey, Rakesh; Lau, Jennifer Y.F.
Abstract: Child labourers are more likely to have experienced physical victimisation, which may increase risk for anxiety/depression, by shaping threat biases in information-processing. To target threat biases and vulnerability for anxiety/depression, we evaluated whether Cognitive Bias Modification (CBM) training could be feasibly and acceptably delivered to rescued youth labourers. Seventy-six physically abused rescued labourers aged 14–17 (40 from Nepal, 36 from India) in out-of-home care institutions received either multi-session computerised CBM or control training. Training targeted attention away from threat to positive cues and the endorsement of benign over threat interpretations. Feasibility and acceptability data were gathered along with pre and post intervention measures of attention and interpretation bias and emotional and behavioural symptoms. In terms of feasibility, uptake (proportion of those who completed the pre-intervention assessment from those who consented) and retention (proportion of those who completed the post-intervention assessment from those who completed the pre-intervention assessment) were above 75% in both countries. Average acceptability ratings were mostly 'moderate' on most indices for both countries, and none of the participants reported experiencing serious adverse events or reactions in response to or during the trial. Secondarily, CBM participants showed increased attention to positive and decreased attention to threatening stimuli, as well as increased endorsement of benign interpretation and decreased endorsement in negative interpretations of ambiguous social situations. Symptom changes were less clear. Delivering CBM to former child labourers in out-of-home care institutions has interventive potential. ClinicalTrials.gov Identifier: NCT03625206, Date of registration: August 10, 2018. Highlights: Abuse in child labourers negatively impacts mental health through threat biases. Rescued youth labourers from India and Nepal completed computerised training. Good response and completion rates among eligible participants were found. Most participants reported the training moderately or highly helpful. Training-linked changes in threat biases in attention and interpretation were variable.